Reconstruction of Secondary Metabolic Pathway to Synthesize Novel Metabolite in Saccharopolyspora erythraea - Ren, Chong-Yang; Liu, Yong; Wei, Wen-Ping; Dai, Junbiao; Ye, Bang-Ce (Frontiers in Bioengineering and Biotechnology, 2021)
Natural polyketides play important roles in clinical treatment, agriculture, and animal husbandry. Compared to natural hosts, heterologous chassis (especially Actinomycetes) have lots of advantages in production of polyketide compounds. As a widely studied model Actinomycete, Saccharopolyspora erythraea is an excellent host to produce valuable heterologous polyketide compounds. However, many factors of host affect the expression efficiency of heterologous genes, it is necessary to modify the host to adapt heterologous production. In this study, the CRISPR-Cas9 system was used to knock out the erythromycin biosynthesis gene cluster of Ab (erythromycin high producing stain). A fragment of 49491 bp in genome (from SACE_0715 to SACE_0733) was deleted, generating the recombinant strain named AbΔery in which erythromycin synthesis was blocked and synthetic substrates methylmalonyl-CoA and propionyl-CoA accumulated enormously. Based on AbΔery as heterologous host, three genes AsCHS, RgTAL, and Sc4CL, driven by strong promoters Pj23119, PermE, and PkasO respectively, were introduced to produce novel polyketide by L-tyrosine and methylmalonyl-CoA. The product (E)-4-hydroxy-6- (4-hydroxystyryl) -3,5-dimethyl-2H-pyrone was identified in fermentation by LC-MS. High performance liquid chromatography analysis showed that knocking out ery BGC resulted an increase of methylmalonyl-CoA by 142% and propionyl-CoA by 57.9% in AbΔery compared to WT, and the yield of heterologous product in AbΔery::AsCHS-RgTAL-Sc4CL was higher than WT::AsCHS-RgTAL-Sc4CL. In summary, this study showed that Ab∆ery could potentially serve as a precious heterologous host to boost the synthesis of other valuable polyketone compounds using methylmalonyl-CoA and propionyl-CoA in the future.